PROFESSIONAL TRAINING OF FUTURE TEACHING STAFF: PHONATION-PHONETIC COMPLEX OF KNOWLEDGE, SKILLS AND ABILITIES - Nataliya V. Pavlova (Russian Journal of Education and Psychology)
Background. In the context of modern changes in the world order, which concerns not only economics, politics, medicine, etc., but also education, the professional training of future teachers, presented in the Decree of the Government of the Russian Federation on the Concept of training teachers for the education system for the period up to 2030, is of great importance. Russian language and literature One of the objectives of the Concept is to increase the importance of the Russian language and Russian literature in teacher training programs. According to the educational training programs, teaching staff must have proficiency in professional written and oral speech in Russian, public speaking skills, the ability to carry out professional communication, that is, possess phonational and phonetic knowledge, skills and abilities.